1987
DOI: 10.3758/bf03205051
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the same/different concept by an African Grey parrot (Psittacus erithacus): Learning with respect to categories of color, shape, and material

Abstract: An African Grey parrot, previously taught to use vocal English labels to discriminate more than 80 different objects and to respond to questions concerning categorical concepts of color and shape, was trained and tested on relational concepts of same and different. The subject, Alex, replied with the correct English categorical label ("color," "shape," or "mah-mah" [matter]) when asked "What's same?" or "What's different?" about pairs of objects that varied with respect to any combination of attributes. His ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
196
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(202 citation statements)
references
References 34 publications
4
196
0
2
Order By: Relevance
“…Katz et al, 2002;Premack and Premack, 1983), S/D judgments can easily be generated from the comparison of only two stimuli. However, such S/D judgments have been difficult to attain in avian species without extensive training (Pepperberg, 1987;Santiago and Wright, 1984). The present results make the case that pigeons, too, can make S/D discriminations based on the successive comparison of only two items.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Katz et al, 2002;Premack and Premack, 1983), S/D judgments can easily be generated from the comparison of only two stimuli. However, such S/D judgments have been difficult to attain in avian species without extensive training (Pepperberg, 1987;Santiago and Wright, 1984). The present results make the case that pigeons, too, can make S/D discriminations based on the successive comparison of only two items.…”
Section: Discussionmentioning
confidence: 59%
“…After learning this discrimination, the degree to which this behavior transfers to novel situations having same and different relations is taken as evidence of concept formation. Using this choice task, it has been found that pigeons, parrots, rhesus monkeys, baboons, and chimpanzees are capable of learning and applying a S/D concept across a wide variety of simultaneously presented visual elements (Bovet and Vauclair, 2001;Cook, 2002a,b;Cook et al, 1995Cook et al, , 1999Cook and Wixted, 1997;Katz et al, 2002;Pepperberg, 1987;Thompson et al, 1997).…”
mentioning
confidence: 99%
“…In recent years, studies of both birds and mammals have revealed even better evidence for the transfer of conceptual same/different discriminations (e.g., Blaisdell & Cook, 2005;Katz, Wright, & Bachevalier, 2002;Mercado, Killebrew, Pack, Macha, & Herman, 2000;Oden, Thompson & Premack, 1988;Pepperberg, 1987;Wright, Cook, Rivera, Sands, & Delius, 1988;see Wasserman, Young, &Cook, 2004 and for reviews). These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003).…”
Section: Same/different Learningmentioning
confidence: 99%
“…The model/rival occasionally errs (produces garbled utterances, partial identifications, etc., that are similar to mistakes being made by the bird at the time For Alex, this problem was resolved through concurrent training or testing on various other capacities in any given session. During training on same/different, the concurrent tasks involved number concepts (Pepperberg, 1987a), additional labels (Pepperberg, 1987b), photograph recognition, and object permanence (Pepperberg & Kozak, 1986)." (Pepperberg, 1988, p. 557 (Hart & Risley, 1995).…”
Section: Behavior Analysis According To Pepperbergmentioning
confidence: 99%